Factors Affecting Adoption of Systematic Household Waste Management, Waste Composting and Homestead Farming in Bharatpur, Janakpur and Pokhara - Sharma, Sharad; Shah, Gita; Aryal, Arjun; Tiwari, Bipan; Khanal, Bharat (Nepalese Journal of Agricultural Sciences, 2026)
SOLID Health project of Nepal Development Society (NeDS) aimed at effective household solid waste management through 3R approach in three mega cities: Bharatpur, Janakpur and Pokhara. On which, non-organic wastes were encouraged to reuse, recycle and safe disposal, whereas organic wastes were attempted to manage through composting at household level and utilizing at homestead farming. The program was executed for around two and half years within the year 2021 to 2024. Major program interventions were capacity enhancement programs, practical demonstration and support with resources. Data were collected from 348 project intervention households through structured surveys, complemented by Focus Group Discussions and Key Informant Interviews. The achievement of the projects was comparatively analyzed with baseline information. Rooftop farming was most prevalent in Pokhara (64%), while kitchen gardening was more common in Bharatpur (71%). Overall, 81% of households across the three cities practiced either rooftop farming, kitchen gardening or both. In overall, there was around 69% percentage change in knowledge and attitude of respondents towards waste management, composting and homestead gardening as compared to baseline status. Composting practice at home was increased significantly in all three cities after project intervention, which was increased by 39% in overall. Also, there was significant adoption of reusing and recycling of the non-organic wastes rather than sending all those to municipality vehicle. Socio-demographic factors such as education level, income, and land availability were significant determinants of adoption. Households with higher education levels and larger homestead land areas showed greater likelihood of practicing kitchen gardening and rooftop farming. A combination of land availability, education levels, economic factors, age group, gender and type of capacity development support approach appear to be the primary drivers behind the differences in adoption rates between three cities